Short-term efficacy of repetitive transcranial magnetic stimulation in SCA3: A prospective, randomized, double-blind, sham-controlled study. (January 2023) - Sikandar, Arif; Liu, Xia-Hua; Xu, Hao-Ling; Li, Ying; Lin, Yun-Qing; Chen, Xin-Yuan; Li, Gui-He; Lin, Min-Ting; Wang, Ning; Chen, Wan-Jin; Ni, Guo-Xin; Gan, Shi-Rui
Abstract: Objective: Spinocerebellar ataxia type 3 (SCA3) is the most common autosomal dominant ataxia globally. No effective treatment is currently available for SCA3. Repetitive Transcranial Magnetic Stimulation (rTMS) is a non-invasive form of brain stimulation, demonstrated to improve symptoms in patients with neurodegenerative cerebellar ataxias. The present study investigated whether treatment with rTMS over the cerebellum for 15 consecutive days improved measures of ataxia in SCA3 patients. Methods: A double-blind, prospective, randomized, sham-controlled trial was carried out on 44 SCA3 patients. Participants were randomly assigned to two groups: real or sham stimulation. Each participant underwent 30 minutes of 1Hz rTMS stimulation (a total of 900 pulses) for 15 consecutive days. The primary outcome measure was the score on the International Cooperative Ataxia Rating Scale (ICARS), and secondary outcomes were from the Scale for the Assessment and Rating of Ataxia (SARA) and the Berg Balance Scale (BBS). Results: Nausea was the only adverse effect reported by 2 participants from the sham and real group. After 15 days of treatment, there was a significant improvement in all performance scores in both real and sham stimulation groups. However, compared to the sham group, the improvements were significantly larger in the real group for the ICARS ( P = 0.002), SARA ( P = 0.001), and BBS ( P = 0.001). Interpretation: A 15 days treatment with rTMS over the cerebellum improves the symptoms of ataxia in SCA3 patients. Our results suggest that rTMS is a promising tool for future rehabilitative approaches in SCA3. Highlights: Low-frequency rTMS over the cerebellum improves symptoms in SAC3 patients. rTMS is well-tolerated in SAC3 patients. Low-frequency rTMS can be used as a therapeutic strategy in SCA3 patients.